2014
DOI: 10.1074/jbc.m114.558049
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the 6-Hydroxy-3-succinoyl-pyridine 3-Monooxygenase Flavoprotein from Pseudomonas putida S16

Abstract: Background: Mechanistic information is limited on pyridine ␤-hydroxylation monooxygenases. Results: The catalytic mechanism of HspB was determined. Conclusion: An observable C (4a) -hydroperoxyflavin intermediate reacts with 6-hydroxy-3-succinoyl-pyridine to form 2,5-dihydroxypyridine and succinate during the catalysis. Significance: This study expands our understanding of pyridine hydroxylases and their pyridine metabolisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Fe-S clusters can be identified from the characteristic absorption peak of purified VppA, and His-tag-specific staining indicated the existence of a [2Fe-2S]-binding subunit. However, no other extra bands were observed by SDS-PAGE, and the UV-visible spectrum did not show the characteristic peak of a flavin cofactor (10). These results suggested that VppA does not have an FAD-binding subunit.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Fe-S clusters can be identified from the characteristic absorption peak of purified VppA, and His-tag-specific staining indicated the existence of a [2Fe-2S]-binding subunit. However, no other extra bands were observed by SDS-PAGE, and the UV-visible spectrum did not show the characteristic peak of a flavin cofactor (10). These results suggested that VppA does not have an FAD-binding subunit.…”
Section: Discussionmentioning
confidence: 63%
“…The pyridine hydroxylases can be subclassified as ␣-, ␤-, or ␥-position hydroxylases according to the hydroxylation position on the pyridine ring (10). VppA is classified as a pyridine ring ␣-position hydroxylase based on its catalytic reaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme is among a few flavin‐dependent monooxygenases that utilize hydroxypyridine compounds as substrates. Other hydroxypyridine–utilizing flavoenzymes include 5PAO, 6‐hydroxy‐3‐succinoyl‐pyridine 3‐monooxygenases (HspB) (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC1/14/13/163.html) , 6‐hydroxynicotinate 3‐monooxygenase (6HN3M) (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC1/14/13/114.html) , 2,6‐dihydroxypyridine 3‐monooxygenase (DHPH) (http://www.chem.qmul.ac.uk/iubmb/enzyme/EC1/14/13/10.html) and the recently reported 5‐hydroxypicolinic acid 2‐monooxygenase (5HP2M) . These enzyme were found in the degradation pathways of pyridine derivatives such as nicotine in soil bacteria .…”
Section: Introductionmentioning
confidence: 99%
“…The activity of HSP hydroxylase was determined using the method of Tang et al [23,30]. The standard reaction mixture, containing 10 mM FAD, 1 mM HSP, 0.5 mM NADH, and 20 mM Tris-HCl buffer (pH 8.5), was preincubated for 2 min and then the reaction was started by adding the purified enzyme.…”
Section: Enzymatic Activity Assaymentioning
confidence: 99%